A quality control study on Company X - Ambayec, Maria Andrea T. (College of Engineering, 2002)
Company "X" which was established in 1963 manufactures different kinds of food ranging from cupcakes, nuts, wafer sticks, cream sandwiches, biscuits and popped corn. With the available data given by the company, popped corn was the chosen product line to be studied and analyzed in this project. The main problem was the high rejection rate in the production of popped corn. To be able to determine causes of rejection, different problem analysis tools were used. Through brainstorming, use of Ishikawa Diagrams and the Failure Mode Effects and Criticality Analysis or FMECA, alongside the data available, three main problems were identified. These were the high moisture content, improper packaging and not meeting the "60-40" rule. Several possible root causes per problem were identified. Design of Experiment was utilized in order to resolve which possible root causes have significant effects on the problems. The results of the DOE showed that relative humidity, room temperature and drying temperature significantly affects moisture content. On the other hand, only sealer temperature was proven to be significantly affecting the quality of packaging. Lastly, the "60-40" rule is affected significantly by drying temperature as well. Statistical Process Control was used to all the three major problems plus the corresponding significant root causes for each major problem. Control charts and process capability analyses were used to establish control and capability. Alternatives were generated based on the results of the Statistical Process Control Analyses. Several alternatives were generate per problem identified. In order to determine which among the alternatives to implement, advantages, and disadvantages were considered per alternative. Also, each alternative was rated accordingly based on the criteria established. Implementation plan for each recommended alternatives was prepared. In general, most of the alternatives generated were to improve monitoring of the root causes found to be out of control and incapable. The results of the statistical process control are as follows : For the high moisture content, the R content control chart is in control, while the X bar control chart is out of control. For the room temperature, the moving range control chart is in control while the X control chart is out of control. The drying temperature moving range control chart is in control and the X control chart is also in control. The relative humidity R control chart is in control while the X bar control chart is out of control. For the improper packaging, the np control chart is out of control. The sealer temperature moving range control chart is in control while the X control chart is out of control. For the unmet "60-40" rule, the np control chart is in control. The drying temperature moving range control chart is in control while the X control chart is out of control. The results of the process capability study are as follows : For the high moisture content, the process is incapable, while the process is incapable and off-centered in attaining the set specifications for room temperature, drying temperature and relative humidity. For the improper packaging problem, the process is incapable and off-centered in meeting the specifications for the sealer temperature. Lastly, for the unmet "60-40" rule problem, the process is incapable and off-centered in meeting the required specification of drying temperature. Several recommendations are proposed. These are : incorporation of statistical process control into the system, improvement of ventilation system and implementation of maintenance scheduling for the sealer.